Microwave curing of core-shell particle reinforced composites - Seah, Xiang Yu (2018)
In a world of modern and advanced technology, engineering industries are constantly growing at a tremendous rate, research on new techniques for manufacturing high-performance composites at an economical and competitive rate. Over the years, autoclave curing has been a common practice for composite curing, but this manufacturing process has a strong appetite for energy and time, causing it to be very expensive. An alternative solution over the conventional thermal curing to reduce the energy consumption and shorten the curing cycle-time is microwave curing. In this final year project, the curing of dispersed core-shell polymer particle (C/SH) modified Glass Fibre Reinforced Polymer (GFRP) prepreg composites was effectively accomplished using microwave curing under controlled parameters such as temperature, curing time and pressure applied to the GFRP. Mode I and Mode II interlaminar fracture toughness tests were later performed on the manufactured GFRP specimen to study the delamination properties of microwave-cured C/SH particle modified GFRP composites.